Leaf Traits of Parashorea malaanonan Along Elevational Gradient in Mount Makiling Forest Reserve, Philippines - Ebale, Marsh Reginald Bico; Hernandez, Jonathan Ogayon; Tinio, Crusty Estoque (Jurnal Sylva Lestari, 2024)
Studying leaf trait variation and relationships along elevational gradients will enhance our understanding of how plants respond to changing environmental conditions. Thus, we analyzed the leaf traits variation in ecologically and economically important Parashorea malaanonan and the potential influence of environmental covariables (rainfall, relative humidity, and air temperature) on leaf traits along an elevational gradient in Mount Makiling Forest Reserve (MMFR). Three sampling sites were selected based on elevation, i.e., low (400–500 masl), mid (500–600 masl), and high (> 600 masl). The leaf samples were collected from seedlings, saplings, and adult trees of P. malaanonan. There was no significant variation in most of the measured leaf traits, leaf area (LA), specific leaf area (SLA), leaf thickness (LT), leaf length-to-width ratio (L:W) across sampling sites, except vein density (VD). The SLA and LT at high elevations are significantly and negatively correlated (r2 = 0.7396). The environmental covariables had a significant (p < 0.05) impact on the leaf traits of P. malaanonan. The observed variation in some leaf traits may have been influenced by the elevation gradient and its associated environmental conditions. Thus, P. malaanonan may have developed adaptive mechanisms to cope with the changing environment. Keywords: conservation, elevational gradients, environmental variables, leaf traits, Parashorea malaanonan